Endoscopy assistants influence the quality of colonoscopy - Holme, Øyvind; Pedersen, Ina Borgenheim; Medhus, Asle W.; Aabakken, Lars; Glomsaker, Tom; Kvamme, Jan Magnus; Løberg, Magnus; Bretthauer, Michael; Seip, Birgitte; Kjellevold, Øystein; Jørgensen, Anita; Furholm, Siv; Hoff, Geir; de Lange, Thomas (Endoscopy, 2018)
Background Colonoscopy performance varies between endoscopists, but little is known about the impact of endoscopy assistants on key performance indicators. We used a large prospective colonoscopy quality database to perform an exploratory study to evaluate differences in selected quality indicators between endoscopy assistants.Methods All colonoscopies reported to the Norwegian colonoscopy quality assurance register Gastronet can be used to trace individual endoscopy assistants. We analyzed key quality indicators (cecum intubation rate, polyp detection rate, colonoscopies rated as severely painful, colonoscopies with sedation or analgesia, and satisfaction with information) for colonoscopies performed between 1 January 2013 and 31 December 2014. Differences between individual assistants were analyzed by fitting multivariable logistic regression models, with the best performing assistant at each participating hospital as reference. All models were adjusted for the endoscopist. Results 63 endoscopy assistants from 12 hospitals assisted in 15 365 colonoscopies. Compared with their top performing peers from the same hospital, one assistant was associated with cecum intubation failure, four with poor polyp detection, nine with painful colonoscopy, 16 with administration of sedation or analgesics during colonoscopy, and three with patient dissatisfaction about information given relating to the colonoscopy. The number of procedures during the study period or lifetime experience as an endoscopy assistant were not associated with any quality indicator.Conclusion In this exploratory study, there was little variation on important colonoscopy quality indicators between endoscopy assistants. However, there were differences among assistants that may be clinically important. Endoscopy assistants should be subject to quality surveillance similarly to endoscopists.